Calibration Factors for Mass Loss of Longitudinal and Transverse Reinforcement in Accelerated Corrosion Process in the Rc Specimens - Saavedra-Flores, E (Springer Science and Business Media Deutschland GmbH, 2024)
As reported in literature, accelerated corrosion process using impressed current technique is widely adopted to corrode the rebar in reinforced concrete specimens in order to characterise the mechanical properties and to study the response of the corroded structure. Often variations are observed between the actual mass loss achieved during accelerated corrosion process and the target mass loss estimated using Faraday’s law. In this paper, an effort has been made to quantify the variations, in terms of calibration factors for the reinforced concrete prism specimens. Three cases viz., Case 1 passing the current through longitudinal rebar by allowing the current to pass through transverse reinforcement, Case 2 passing the current through the longitudinal rebar by insulating the transverse rebar connection and Case 3 passing the current through longitudinal as well as transverse rebar separately by insulating the connection between rebars. Calibration factors for longitudinal and transverse rebars are obtained for the three cases considered. Further, the yield strength (fy), ultimate tensile strength (fu), and elongation (δc) of the corroded rebars of the specimens investigated are obtained. The constants for fy, fu,δc, called here as α1,α2,α3, respectively, are estimated in the present study and comparisons have been made with values obtained from existing models in literature. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.